Nucleosomes, histones & chromatin. - Wu, Carl; Allis, C. David (Methods in enzymology, 2012)
This new volume of Methods in Enzymology continues the legacy of this premier serial by containing quality chapters authored by leaders in the field. The first of 2 volumes covering Nucleosomes, Histones & Chromatin and has chapters on Methods applied to the study of Protein Arginine Methylation, High resolution identification of intra- and interchromosomal DNA interactions by 4C technology, and Peptide arrays to interrogate the binding specificity of chromatin-binding proteins. Continues the legacy of this premier serial by containing quality chapters authored by leaders in the field The first of 2 volumes covering nucleosomes, histones and chromatin Chapters on methods applied to the study of protein arginine methylation, high-resolution identification of intra- and interchromosomal DNA interactions by 4C technology, and peptide arrays to interrogate the binding specificity of chromatin-binding proteins.